SUSTAIBILITY OF TURTLE HARVESTING Cuora amboinensis DAUDIN 1802 (TESTUDINES: GEOMYDIDAE) IN EXPLOITED AREA, EAST BORNEO - Nuryani Widagti (Pusbindiklat - LIPI, 2011)
Research on harvesting of a freshwater turtle (Cuora amboinensis) in Kota Bangun Sub district was conducted in June till August 2006. The research aims to estimate the number of harvesting, to describe trading mechanism, and to make Non-Detriment Finding (NDF) of C. amboinensis in Kota Bangun Sub district. Method used was harvest survey and interview. During the study, a total of 1,388 individuals were collected, comprising 46.97% adult females, 48.7% adult males, and 4.32% juveniles. It indicated that larger individuals of C. amboinensis are preferably collected for trade in study site. Base on the number of middlemen, the average of harvest-yield in Kota Bangun Sub district and its surroundings are about 622 individuals/month. There are four levels of trade structure in Kota Bangun Sub district, i.e trappers, collectors, middlemen, and exporter.